Social capital and periodontal disease in Hispanic/Latino adults in the United States: Results from the Hispanic Community Health Study/Study of Latinos. (1st March 2020) - Laniado, Nadia; Badner, Victor M.; Sanders, Anne E.; Singer, Richard H.; Finlayson, Tracy L.; Hua, Simin; Kaste, Linda M.; Isasi, Carmen R.
Abstract: Aims: To examine the association of social capital with periodontal disease severity. Materials and Methods: We analysed data obtained from 3, 994 men and women aged 18–74 years in the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study (HCHS/SOL SCAS). From 2008 to 2011, dentists assessed periodontitis status with a full‐mouth periodontal examination. Periodontitis was classified using standardized case definitions. Multivariable logistic regression estimated odds of moderate–severe periodontitis associated with two measures of social capital: structural support (Social Network Index) and functional support (Interpersonal Support Evaluation List). Results: For US‐born participants, for each additional person in their social network, the adjusted odds of moderate–severe periodontitis was reduced 17% (OR = 0.83, 95% CI = 0.71, 0.96). However, no association was found between functional support and periodontal disease severity. Conclusions: Greater structural social support was associated with a lower prevalence of moderate–severe periodontitis in US‐born Hispanics/Latinos. These findings suggest that US‐born Hispanics/Latinos with less social support represent a vulnerable segment of the population at high‐risk group for periodontal disease.